Innovating academic writing through flipped classroom instruction - Junio, Dylyn A. (Animo Repository, 2019)
Flipped Classroom Instruction has become a trend and a popular instructional model of the recent time in which the typical lecture and homework features of a course are inverted. This method transforms classroom pedagogy into dynamic and interactive manner where the teacher guides and facilitates students' learning process. The present study investigates the students' perceptions on flipped classroom instruction in academic writing class in contrast to traditional teaching. To achieve this, an instructional design infused with multimedia tools in writing lessons were provided and implemented in writing classes. The mixed method was used to collect qualitative and quantitative data. The results revealed a positive impact of flipped learning to students which also indicate their improved academic writing skills in certain ways.© 2019 IEEE.